Availability and Utilisation of information and communications technology for Effective Learning Habits among Secondary School Students - Hameed Olalekan Bolaji; Joshua Durotoye Jolaoye (Universitas Pendidikan Indonesia (UPI), 2022)
The study investigated the availability and utilization of information and communications technology (ICT) facilities for effective learning habits among Secondary School students in Kwara State, Nigeria. The findings revealed that many of the ICT facilities needed for the learning habit are not available. The consequence is that secondary school students are more likely to use ICT tools when they are readily available, which promotes effective learning habits. It was also revealed that the majority of the facilities needed for the learning habit are not being used by the teachers. Moreover, it was revealed that there was a significant relationship between the availability and utilization of ICT and effective learning habits among secondary school students. According to the findings, ICT access and use among secondary school students in Kwara State are crucial to their academic progress, daily activities in school, and life after graduation. It was recommended among others that government should encourage effective learning habits among students in secondary schools, and the government should hire technicians to fix and maintain the ICT facilities utilized in classrooms.